Indian Council of Medical Research consensus document for the management of tongue cancer - Anil K D′Cruz; Shilpi Sharma; Jaiprakash P Agarwal; Alok Thakar; Ashraf Teli; Supreeta Arya; Chirag Desai; Pankaj Chaturvedi; Paul Sebastian; Bipin T Verghese; Shubhada Kane; V Sucharita; et al. (Indian Journal of Medical and Paediatric Oncology)
The document is based on consensus among the experts and best available evidence pertaining to Indian population and is meant for practice in India. Early diagnosis is imperative in improving outcomes and preserving quality of life. High index of suspicion is to be maintained for leukoplakia (high risk site). Evaluation of a patient with newly diagnosed tongue cancer should include essential tests: Magnetic resonance imaging (MRI) is investigative modality of choice when indicated. Computed tomography (CT) scan is an option when MRI is unavailable. In early lesions when imaging is not warranted ultrasound may help guide management of the neck. Early stage cancers (stage I & II) require single modality treatment - either surgery or radiotherapy. Surgery is preferred. Adjuvant radiotherapy is indicated for T3/T4 cancers, presence of high risk features [lymphovascular emboli (LVE), perineural invasion (PNI), poorly differentiated, node +,close margins). Adjuvant chemoradiation (CTRT) is indicated for positive margins and extranodal disease. Locally advanced operable cancers (stage III & IVA) require combined multimodality treatment - surgery + adjuvant treatment. Adjuvant treatment is indicated in all and in the presence of high risk features as described above. Locally advanced inoperable cancers (stage IVB) are treated with palliative chemo-radiotherapy, chemotherapy, radiotherapy, or symptomatic treatment depending upon the performance status. Select cases may be considered for neoadjuvant chemotherapy followed by surgical salvage. Metastatic disease (stage IVC) should be treated with a goal for palliation. Chemotherapy may be offered to patients with good performance status. Local treatment in the form of radiotherapy may be added for palliation of symptoms. Intense follow-up every 3 months is required for initial 2 years as most recurrences occur in the first 24 months. After 2 nd year follow up is done at 4-6 months interval. At each follow up screening for local/ regional recurrence and second primary is done. Imaging is done only when indicated.